(untitled) (Journal of the College of Basic Education, 2022)
In this work a Schiff base ester derived ligand [H2L1] were synthesized in three steps, first Synthesis of the pentanoiyl chloride from reaction thionyl chloride with pentanoic acid. in the second step the precursosr (W1), 4-[3-(3-hydroxy-1-methyl- butylideneamino)- 4-methyl-phenylimino]-pentan-2-ol ,was prepared by the reaction of acetylaceton with tolylen2,4-diamin . In the theird step the ligands were synthesized by the reaction of precursor (W1)with pentanoiyl chloride to produce[H2L1] 1:2 mole ratio. The binuclear complexes with Cr3+, Co2+ and Zn2+, were synthesized by the reaction of the ligand with metal salts in 1:1 mole ratio. The compounds were characterized by spectroscopic methods [FT-IR, UV-Vis, CHN, 1H-NMR] elemental analysis, along with conductivity, and melting point measurements. The structure of the complexes were obtained according to the previous studies. Finally the liquid crystalline properties of the prepared compounds were studied by hot stag and DCS.